Implementation of the Campaign Monitoring Policy by the Election Supervisory Agency of Blitar City in the 2024 Simultaneous Regional Elections - Muhammad Fa’iq Firiznanda; Indira Arundinasari (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Supervision of campaign stages in the 2024 Simultaneous Regional Elections in Blitar City is the task and responsibility of the Blitar City General Election Supervisory Body. The lack of human resources in carrying out supervision raises the question of whether the Blitar City Bawaslu has implemented the campaign stage supervision policy properly. The purpose of this study was to determine the success of the implementation of the campaign stage supervision policy by the Blitar City Bawaslu in the 2024 Simultaneous Regional Elections. By using qualitative research methods, and data collection using observation and interview methods. This study uses the implementation theory by George C. Edwards III which has four main indicators, namely: communication, resources, disposition, and bureaucratic structure. The results of this study indicate that the implementation of the campaign stage supervision policy by the Blitar City Bawaslu in the 2024 Simultaneous Regional Elections has been implemented well, although there are still several challenges. Keywords: Bawaslu of Blitar City, Campaign Stage Supervision, Policy Implementation